1990
DOI: 10.3109/15513819009067127
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Visceral Fibrosis Accompanying the Megakaryoblastic Leukemoid Reaction of Down Syndrome

Abstract: Two infants with Down syndrome, one 4 weeks old and the other stillborn, at necropsy showed hepatic and pancreatic fibrosis, which was very severe in the liver of the liveborn infant and in the pancreas of the stillbirth. The liveborn infant had typical hematological features of the transient congenital leukemoid reaction of Down syndrome, and the identification of a megakaryoblastic component was consistent with recent opinion that this is a spontaneously-remitting congenital megakaryoblastic leukemia. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 22 publications
3
44
0
1
Order By: Relevance
“…43 However, most newborns with DS never develop TL. Of those who do, our study indicates that about 60% will experience a spontaneous and continuous remission, about 20% will experience early death [20] 48XXϩ21cϩ21 [11]; 47XYϩ21c [9] 2-AMKL 47XYϩ21cdel(16)(q21) [4]; 47XYϩ21c [16] 47XYϩ21c [12] 3-AMKL 48XYϩ21cϩ11 [4]; 47XYϩ21c [16] 48XYϩ21cϩ11 [8] 4-AMKL 47XYϩ21c [26]; 45-46XYϩ21c [4] (random loss) 48XYϩ21cϩ8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 However, most newborns with DS never develop TL. Of those who do, our study indicates that about 60% will experience a spontaneous and continuous remission, about 20% will experience early death [20] 48XXϩ21cϩ21 [11]; 47XYϩ21c [9] 2-AMKL 47XYϩ21cdel(16)(q21) [4]; 47XYϩ21c [16] 47XYϩ21c [12] 3-AMKL 48XYϩ21cϩ11 [4]; 47XYϩ21c [16] 48XYϩ21cϩ11 [8] 4-AMKL 47XYϩ21c [26]; 45-46XYϩ21c [4] (random loss) 48XYϩ21cϩ8…”
Section: Discussionmentioning
confidence: 99%
“…5-ALL 47XXϩ21c [20] 47XXϩ21c [20] 6-AMKL 47XYqs,del(13)(q13q31)ϩ21 [20]/46XYqs [3] 47XYqs,ϩ21del(13)(q13q31), add (17) 7-AMKL* 47XYϩ21c [20] 47XYϩ21c,isochrome 7(q10) [12] 8-AMKL 47XYϩ21c [20] 49XYϩ21cϩ21ϩ8 [9]/47XYϩ21c [11] 9-AMKL 46XYder(14;21)(q10:q10)cϩ21c [5] 46XY der(14;21)(q10:q10)cϩ21c [5]/46XYder(7)t(1;17)(q21;q36),der(14;21)(q10;q10)cϩ21c [5] ALL indicates B-precursor acute lymphoblastic leukemia. *The one patient who died despite intensive therapy.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…4a, b), autopsy cases of patients with TL have demonstrated that these patients often exhibit unusual diffuse sinusoidal liver fibrosis (Fig. 4c, d), but not myelofibrosis (Becroft & Zwi, 1990;Ruchelli et al, 1991;Miyauchi et al, 1992;Yagihashi et al, 1995;Schwab et al, 1998;Shiozawa et al, 2004). It has been shown that leukemic blasts in AMKL produce cytokines, including platelet-derived growth factor (PDGF), platelet factor 4 and transforming growth factor β (TGFβ) that stimulate fibroblasts in the bone marrow causing myelofibrosis (Breton-Gorius et al, 1982;Roberts et al, 1986;Sunami et al, 1987;Terui et al, 1990).…”
Section: Origin Of Leukemic Progenitors and Association With Hematopomentioning
confidence: 99%
“…infantile cases, as well as stillborns with evidence of TMD [7][8][9][10][11][12]. Indeed, TMD may originate during intrauterine life, since several cases have been diagnosed on the basis of hydrops fetalis as early as the 27th week of gestation [13,14]. As is true for its course, the pathophysiologic mechanisms resulting in occurrence of TMD remain obscure.…”
Section: Introductionmentioning
confidence: 99%